Concept of Adulteration and Substitution of Drugs in Unani System of Medicine - Anju; Rasikh Javaid; Ghazala Javed (International Journal of Pharma and Bio Sciences, 2020)
The adulteration and substitution of herbal drugs have become a menace nowadays. It affects the quality of Unani medicine in general and confidence among the public in particular. There are many factors responsible for this state of affairs. Of these some are deliberate, especially market-driven and some non-deliberate, due to ignorance or accident. Sometimes incorrect identification of various plant species has resulted in adulteration and substitution of some Unani drugs. The concept of substitution and adulteration (Badal) prevailed since ages in Unani classical literature. It has been described in detail by Buqrat (Hippocrates) (460-377 BC), Jalinoos (Galen) (129-210 AD), Ibn Sina (Avicenna) (980-1037 AD) etc. Some eminent Unani Physicians exclusively wrote on this subject. Zakariya Mohammad Al-Razi Al Rhazaes (865-925 AD) treatise titled “Kitab al Abdal” is the best example. The substitution of each and every single drug (mufradat) was given in almost all writings on Ilmul Advia, and therefore, it became a trend in the successive writings on Ilmul Advia. It was followed by Ibn Sina in “Al-Qanun fit Tib”, Ibn Baitar (1197-1248 AD) in “Jamiul Mufradat”, Najm-ul-Ghani in “Khazain-ul-Advia” and also by Kabiruddin (1894-1976 AD) in his book “Kitabul Mufradat”. In this review article, the issue of adulteration and substitution in Unani drugs and its implication vis a vis Drugs and Cosmetics Act, 1940 and Rules, 1945 shall be discussed.